Spanish courts jurisdiction in international distribution contractual claims: the auto Court of Appeal of Asturias of 25th May 2020 - Goñi Urriza, Natividad (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
In a case concerning a distribution contract to be performed in Spain, the Court of Appeal of Asturias (Audiencia Provincial of Asturias) amends the decision of the first instance Court of Castropol to decline jurisdiction over a contractual claim on the ground that article 51 LEC should be applied as a consequence of Rome I Regulation. Dismissing this approach and considering that jurisdiction must be examined in the light of Brussels I Bis Regulation, the Court of Appeal carries out a twofold analysis: one focused on the scope of application of the BIR, and another on the applicability of the second paragraph of article 7(1)(b) BIR under the jurisprudence of the European Court of Justice.